2017
DOI: 10.1002/ange.201704487
|View full text |Cite
|
Sign up to set email alerts
|

A T‐Shaped Nickel(I) Metalloradical Species

Abstract: A T‐shaped NiI complex was synthesized using a rigid acridane‐based pincer ligand to prepare a metalloradical center. Structural data displays a nickel ion is embedded in the plane of a PNP ligand. Having a sterically exposed half‐filled dx2-y2 orbital, this three‐coordinate NiI species reveals unique open‐shell reactivity including the homolytic cleavage of various σ‐bonds, such as H−H, N−N, and C−C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 62 publications
(18 reference statements)
2
12
0
Order By: Relevance
“…The Natural Population Analysis (NPA), Mulliken population, and LCAO-MO analyses reveal that the SOMO has essentially a d x 2 −y 2 character in all the complexes (Figure 6 and Tables S11 and S14), which resembles the Ni I complexes reported by Lee and Gade. 65,92 In combination with higher calculated spin density at the halogen atoms, this is also in accordance with more pronounced superhyperfine splitting from halogens observed in EPR spectra of square planar complexes 7 and 8 compared to bent complexes 5 and 6. In Lee's case, T-shaped complexes could be obtained for Ni complexes bearing anionic PNP ligands having a central amide donor, where no ligands were present in trans position to that amide.…”
Section: ■ Introductionsupporting
confidence: 81%
“…The Natural Population Analysis (NPA), Mulliken population, and LCAO-MO analyses reveal that the SOMO has essentially a d x 2 −y 2 character in all the complexes (Figure 6 and Tables S11 and S14), which resembles the Ni I complexes reported by Lee and Gade. 65,92 In combination with higher calculated spin density at the halogen atoms, this is also in accordance with more pronounced superhyperfine splitting from halogens observed in EPR spectra of square planar complexes 7 and 8 compared to bent complexes 5 and 6. In Lee's case, T-shaped complexes could be obtained for Ni complexes bearing anionic PNP ligands having a central amide donor, where no ligands were present in trans position to that amide.…”
Section: ■ Introductionsupporting
confidence: 81%
“…By incorporating this central six‐membered N ‐heterocycle, the bite angle of the pincer is reduced in comparison to Cbz ( R PNP)H without affecting the co‐planarity of the three donor atoms. Hence, MeAcr ( R PNP) seems to be perfectly pre‐organized for the formation of mer ‐octahedral, square planar or T‐shaped pincer complexes . For its Ru, Ni and Co complexes, these geometries have been found, while a very recent study on MeAcr ( R PNP)‐coordinated Ti complexes clearly demonstrated that the ligand also supports distorted trigonal‐bipyramidal coordination geometries, with the metal ion being displaced significantly from the plane through the three donor atoms.…”
Section: N‐heterocyclic Pnp Pincers: An Overviewmentioning
confidence: 97%
“…CO or PMe 3 ) are readily bound to the free coordination site. For a number of small molecules, homolytic bond activations have been observed and the products of these reactions ( 54 and 55 ) were identified, also for the cases, which led to the formation of equimolar mixtures (X ≠ Y, see Scheme ) …”
Section: Pnp Pincers and Their Reactivity Patternsmentioning
confidence: 99%
See 2 more Smart Citations